Application of RSM and Taguchi methods for optimizing the transesterification of waste cooking oil catalyzed by solid ostrich and chicken-eggshell derived CaO - Tan, Yie Hua; Abdullah, M.O.; Nolasco-Hipolito, C.; Ahmad Zauzi, N.S. (2017)
© 2017 Elsevier Ltd This paper reported the optimization of biodiesel production from waste cooking oil catalyzed by solid ostrich-eggshell and chicken-eggshell derived CaO via transesterification process using response surface methodology (RSM) and Taguchi method. Quadratic polynomial equations were obtained for transesterification reaction. Independent variables i.e. molar ratio of methanol to oil (M:O), catalyst concentration, reaction temperature and reaction time were investigated. It was found that the most influential parameter on the biodiesel production was reaction temperature based on both RSM and Taguchi method. The optimum biodiesel yield of ∼98% (ostrich eggshell) and ∼96% (chicken eggshell) were achieved at M:O of ∼10:1; catalyst concentration of ∼1.5 %w/v; reaction temperature of 65 °C; and reaction time of ∼2 h for RSM and Taguchi method, respectively.